(untitled) (Colombia Medica, 2014)
Introduction The study aim was to determine the frequency of prenatal ultrasound diagnosis of congenital anomalies in Newborns (NB) with birth defects hospitalized in two Neonatal Intensive Care Units (NICU) of Cali (Colombia) and to identify socio-demographic factors associated with lack of such diagnosis. Patients and methods It was an observational cross-sectional study. NB with congenital defects diagnosable by prenatal ultrasound (CDDPU), who were hospitalized in two neonatal intensive care units (NICU), were included in this study. A format of data collection for mothers, about prenatal ultra-sonographies, socio-demographic data and information on prenatal and definitive diagnosis of their conditions was applied. Multiple logistic and Cox regressions analyses were done. Results 173 NB were included, 42.8% of cases had no prenatal diagnosis of CDDPU; among them, 59.5% had no prenatal ultrasound (PNUS). Lack of PNUS was associated with maternal age, 25 to 34 years (Odds Ratio [OR]: 4.41) and 35 to 47 years (OR: 5.24), with low levels of maternal education (OR: 8.70) and with only a PNUS compared to having two or more PNUS (OR: 4.00). Mothers without health insurance tend to be delayed twice the time to access the first PNUS in comparison to mothers with payment health insurance (Hazard Ratio [HR]: 0.51). Among mothers who had PNUS, screening sensitivity of CDDPU after the 19thgestational week was 79.2%. Conclusions The frequency of prenatal diagnosis is low and is explained by lack of PNUS, or by lack of diagnostic in the PNUS. An association between lack of PNUS and late age pregnancy and low level of maternal education was found. In addition, uninsured mothers tend to delay twice in accessing to the first PNUS in comparison to mothers with health insurance. It is necessary to establish national policies which ensure access to appropriate, timely and good quality prenatal care for all pregnant women in Colombia.